Success made simple : an inside look at why Amish businesses thrive - Wesner, Erik, 1978- (Jossey-Bass, 2010)
The keys to better business from a thriving group of business owners-the Amish. Business can be discouraging. According to US Department of Labor figures, only 44 percent of newly-opened firms will last four years. Amish firms, on the other hand, have registered a 95% survival rate over a five-year period. And in many cases, those businesses do remarkably well-as Donald Kraybill writes: "the phrase 'Amish millionaire' is no longer an oxymoron." Success Made Simple is the first practical book of Amish business success principles for the non-Amish reader. The work provides a platform o.